A comparative study of the formation, and ion and solvent transport of polyaniline in protic liquid-based deep eutectic solvents and aqueous solutions using EQCM. (20th June 2022) - Ismail, Hani K.; Alesary, Hasan F.; Juma, Jamil A.; Hillman, A. Robert; Ryder, Karl S.
Abstract: Electroactive polymers such as polyaniline, polypyrrole and poly(3, 4-ethylenedioxythiophene) have many potential applications, but the nature of the electrolyte can be adversely affected on mass transport processes – of electronic charge, electroneutrality counter-ions ("charge-balancing"), reactant species, and mobility of polymer segments. In this study, polyaniline (PANI) films have been prepared in deep eutectic solvent (Oxaline, a eutectic mixture of oxalic acid and choline chloride) and acidic aqueous media using cyclic voltammetry associated with the electrochemical quartz crystal microbalance (EQCM). PANI was found to grow in both liquids although the rate of growth was slower in Oxaline than aqueous acid due to the higher viscosity of the former. The results showed that PANI electrodes made in aqueous solutions grow by an autocatalytic mechanism, unlike those in deep eutectic solvents (DESs). The stability and durability of some films was examined in DESs and aqueous solutions at 25 °C and 50 °C. The results showed the mobile species are different when cycled in the DES compared to aqueous media. For films grown in different media but cycled in aqueous acid, the anion (HSO4 − ) was found to dominate the mobile species. However, the mass behaviour of PANI electrodes (deposited from aqueous/Oxaline-DES) in DESs (Ethaline) at 50 °C was most strongly associated with cation (Ch + ) egress ( i.e., mass decrease) during the oxidation reaction and cation (Ch + ) ingress ( i.e., mass increase) during the reduction reaction. In addition, the results showed that temperature plays an important role in increasing the rate of diffusion and the stability of mass change in viscous ionic liquids. Graphical abstract: Image, graphical abstract